Determinants of bank profitability: A comparative study of East Asia and Latin America - Ahmad, R.; Koh, E.H.Y.; Shaharuddin, S.S. (Inderscience, 2016)
This paper identifies the determinants of profitability using an unbalanced panel of 78 East Asian and 89 Latin American banks for the period 2003-2014. We regress profitability against bank-specific variables (capital adequacy, cost-income ratio, liquidity ratio, loan loss reserve ratio, and bank size) and macroeconomic variables (gross domestic product, inflation and bank concentration). Our dynamic panel regression model suggests that bank profitability in East Asia is determined by more bank-specific variables than macroeconomic variables; the reverse, however, applies to Latin America. We contribute to current literature by: 1) using a more robust profitability measure (risk-adjusted returns); 2) employing both bank-specific and macroeconomic variables; 3) studying two large and fast-developing regions of East Asia and Latin America. Our findings enhance our theoretical and practical knowledge of bank-specific profitability determinants. It also enables policy makers to deliberate on the pertinent macroeconomic determinants such as inflation and concentration ratio.